Divergent Patterns of Bacterial Community Structure and Function in Response to Estuarine Output in the Middle of the Bohai Sea - Wang, Caixia; Zhang, Haikun; Liu, Pengyuan; Wang, Yibo; Sun, Yanyu; Song, Zenglei; Hu, Xiaoke (Frontiers in Microbiology, 2021)
Understanding environment-community relationships under shifting environmental conditions helps uncover mechanisms by which environmental microbial communities manage to improve ecosystem functioning. This study investigated microbial community and structure near the Yellow Sea River estuary in 12 stations across the middle of the Bohai Sea, over two seasons to elucidate the influence of estuarine output on them. We found that the dominant phyla in all stations were Proteobacteria, Cyanobacteria, Bacteroidetes, Actinobacteria and Planctomycetes. Alpha-diversity increased near the estuary and bacterial community structure differed with variation of spatiotemporal gradients. Among all environmental factors surveyed, temperature, salinity, phosphate, silicon, nitrate and total virioplankton abundance played crucial roles in controlling bacterial community composition. Some inferred community functions such as carbohydrate, lipid, amino acid metabolism, xenobiotics biodegradation, membrane transport and environmental adaptation were much higher in winter, energy and nucleotide metabolism were lower in winter. Our results suggested that estuarine output had a great influence on the Bohai Sea environment and changes in water environmental conditions caused by estuarine output developed distinctive microbial communities in the middle of the Bohai Sea. The distinctive microbial communities in winter demonstrated that the shifting water environment may stimulate changes in the diversity and then strengthen the predicted functions.